Secrets to Student Success: The Relationship of Intrapersonal, Interpersonal, and Intrinsic Motivation - Christien Adriani Karambut; Jacob Tateol Silangen Makapedua; Daisy Iriany Erny Sundah (Eduvest - Journal of Universal Studies, 2025)
Intrapersonal and interpersonal intelligence are essential soft skills for students, playing a crucial role in helping them navigate academic and social challenges while developing personal qualities necessary for success in the workplace. These intelligences are vital for graduates, enabling them to interact effectively with colleagues, superiors, and clients, as well as manage themselves in a dynamic work environment. This study aims to analyze the intrapersonal and interpersonal intelligence and intrinsic motivation of students majoring in Business Administration at Manado State Polytechnic using a descriptive research method. The study population consists of 108 students from the D3 Business Administration program, and a census sampling technique was applied due to the relatively small population size. The findings indicate that respondents' perceptions of intrapersonal intelligence are categorized as high or good, with most indicators rated positively except for the independence indicator, which falls into the moderate category. Similarly, respondents' perceptions of interpersonal intelligence are classified as high or very good. Additionally, the average perception of intrinsic motivation is also categorized as high or very good, with both indicators and statement items receiving very good ratings.